Conflict and Resource Development in the Southern Highlands of PNG - Haley, Nicole (Studies in State and Society in the Pacific, 2007)
The Southern Highlands is one of Papua New Guinea's most resource-rich provinces, but for a number of years the province has been riven by conflict. Longstanding inter-group rivalries, briefly set aside during the colonial period, have been compounded by competition for the benefits provided by the modern state and by fighting over the distribution of returns from the several big mining and petroleum projects located within the province or impinging upon it. Deaths from the various conflicts over the past decade number in the hundreds. As a result of inter-group fighting, criminal activity and vandalism, a number of businesses have withdrawn from the province. Roadblocks and ambushes have made travel dangerous in many parts and expatriate missionaries and aid workers have left. Many public servants have abandoned their posts with the result that state services are not provided. Corruption is rife. Police are often reluctant to act because they are outnumbered and outgunned. This volume brings together a number of authors with deep experience of the Southern Highlands to examine the underlying dynamics of resource development and conflict in the province. Its primary purpose is to provide some background to recent events, but the authors also explore possible approaches to limiting the human and economic costs of the ongoing conflict and breakdown of governance.